Region‐specific insular volumetric decreases in drug‐naive, first‐episode schizophrenia and their unaffected siblings. Issue 2 (18th October 2019) - Li, Huabing; Ou, Yangpan; Liu, Feng; Su, Qinji; Zhang, Zhikun; Chen, Jindong; Zhu, Furong; Zhao, Jingping; Guo, Wenbin
Abstract: Decreased insular volume may be one of the anatomical alterations caused by schizophrenia. The possibility of region‐specific insular volumetric reduction as an endophenotype and/or a possible treatment predictor is a critical issue with great implications for the diagnosis and prognosis of the disease. The sample of the current study comprised 44 drug‐naive and first‐episode patients, 42 unaffected siblings, and 44 healthy controls. A computational anatomy toolbox (CAT12) was applied to analyze the structural images with a fine‐grained, cross‐validated brainnetome atlas. Correlation analysis and support vector regression (SVR) were used to determine the relationship between insular deficits and symptomatic severity among patients. The gray matter volume (GMV) values in the left hypergranular insula (G) exhibited the following pattern: patients < siblings < controls. GMV values in the right ventral agranular insula (vIa) and baseline Positive and Negative Syndrome Scale negative symptoms subscale scores among patients showed a positive correlation ( r = 0.384, p = .010). Further SVR analysis exhibited a significantly positive correlation between GMV values in the right vIa and negative symptomatic improvement among patients ( r = 0.537, p < .001). Results suggested the presence of region‐specific insular volumetric decreases in first‐episode schizophrenia. Thus, volumetric decrease in left G might be a potential endophenotype for schizophrenia, and GMV values in right vIa might be used to predict negative symptomatic improvement in schizophrenia.